2018
DOI: 10.3390/ma11112331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Samarium on the Microstructure and Corrosion Resistance of AZ91 Magnesium Alloy Treated by Ultrasonic Vibration

Abstract: The effects of samarium (Sm) on the microstructure and corrosion behavior of AZ91 magnesium alloy treated by ultrasonic vibration were investigated by scanning electron microscopy, X-ray diffraction, transmission electron microscopy, and electrochemical measurements. The results showed that the addition of Sm resulted in the formation of Al2Sm, which reduced the volume fraction of the β-Mg17Al12 phase and changed its morphology to fine granular. The AZ91–Sm alloys treated by ultrasonic vibration revealed relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It can prevent the penetration of chloride ions into the substrate . The samarium conversion coating and the Sm-incorporated AZ91 alloy showed enhanced corrosion resistance, which is consistent with our results. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can prevent the penetration of chloride ions into the substrate . The samarium conversion coating and the Sm-incorporated AZ91 alloy showed enhanced corrosion resistance, which is consistent with our results. , …”
Section: Resultsmentioning
confidence: 99%
“…22 The samarium conversion coating and the Sm-incorporated AZ91 alloy showed enhanced corrosion resistance, which is consistent with our results. 23,24 3.2.1. Localized Electrochemical Impedance Spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding its corrosive performance, Dargusch et al [24] reported that the use of the ultrasonic technology refined grain size which then resulted in a lower in corrosion rate in vivo . Additionally, the refining process effectively reduces the Mg 17 Al 12 volume fraction while promoting thinner and smaller intermetallics, contributing to a uniform corrosion layer [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Mg matrix composites that are reinforced by adding particles and whiskers feature a good specific modulus, specific strength, wear resistance, adjustable linear expansion coefficient, and so on. Therefore, they have great potential applications in aerospace, military electronics, automotive, orbital, and other fields [5,6,7,8,9]. Commonly used reinforcing particles and whiskers include: SiCp [10], TiCp [11], B 4 Cp [12], SiCw [13], Ce [14], etc.…”
Section: Introductionmentioning
confidence: 99%